2021
DOI: 10.1101/2021.06.08.446897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The transcription factor Roc1 is a regulator of cellulose degradation in the wood-decaying mushroom Schizophyllum commune

Abstract: Wood-decaying fungi of the class Agaricomycetes (phylum Basidiomycota) are saprotrophs that break down lignocellulose and play an important role in the nutrient recycling. They secrete a wide range of extracellular plant cell wall degrading enzymes that break down cellulose, hemicellulose and lignin, the main building blocks of plant biomass. Although the production of these enzymes is regulated mainly at the transcriptional level, no activating regulators have been identified in any wood-decaying fungus in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…We also found that the C. cinerea ortholog (protein ID: 447627) of the S. commune roc1 transcription factor was significantly upregulated in both mutants. Roc1 was recently described as a regulator of cellulase genes in S. commune (Marian et al ., 2021). Similarly, a heat shock factor-type gene (protein ID: 523533) related to the S. cerevisiae skn7 transcription factor was upregulated in both mutants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found that the C. cinerea ortholog (protein ID: 447627) of the S. commune roc1 transcription factor was significantly upregulated in both mutants. Roc1 was recently described as a regulator of cellulase genes in S. commune (Marian et al ., 2021). Similarly, a heat shock factor-type gene (protein ID: 523533) related to the S. cerevisiae skn7 transcription factor was upregulated in both mutants.…”
Section: Resultsmentioning
confidence: 99%
“…These transcription factors include ones specifically responsible for the activation of substrate-specific sets of enzyme-encoding PCWDEs, such as xylanases, cellulases, pectinases (Benocci et al ., 2017, Thieme et al ., 2017, Klaubauf et al ., 2014). While several TFs regulating specific PCWDE genes have been described in the Ascomycetes, only a single gene, Roc1 of S. commune (Marian et al ., 2021) has been associated with cellulose degradation in the Basidiomycota. Our data revealed several transcription factors that are differentially expressed in C. cinerea cre1 mutants, providing candidates for novel TFs related to plant biomass utilisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains and culture conditions: three strains of Schizophyllum commune were used. The reference strain 4.8A, as well as LoenenD and TattoneD (Marian et al, 2021;. Strains were cultured at 25ºC on Schizophyllum Complete Media (SCM) except where noted below (Dons et al, 1979).…”
Section: Methods: Culture Conditionsmentioning
confidence: 99%